Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I know we can transform a second order PDE into three standard forms. But how to deal with the remaining first order terms?

Particularly, how to solve the following PDE:

$$ u_{xy}+au_x+bu_y+cu+dx+ey+f=0 $$

update:

$a,b,c,d,e,f$ are all constant.

share|improve this question
    
$a$ , $b$ , $c$ , $d$ , $e$ and $f$ are constants or functions of $x$ and $y$ ? –  doraemonpaul Nov 2 '12 at 14:58
    
@doraemonpaul constant –  hxhxhx88 Nov 3 '12 at 2:59
    
First find and solve the special cases that can treat as ODE to solve. Then try to introduce some kind of variable transformations e.g. let $u(x,y)=f(x)g(y)v(x,y)$ to research the transforming ability to a PDE that can treat as ODE to solve. –  doraemonpaul Nov 3 '12 at 22:18
    
Whithout boundary conditions, it is hard to say. A trivial solution would be $$u(x,y) = -\frac{d}{c}x -\frac{e}{c}y -\frac{f}{c} + \frac{ad +be}{c^2}.$$ –  Pragabhava Nov 7 '12 at 2:41

1 Answer 1

up vote 0 down vote accepted

Case $1$: $a=b=c=0$

Then $u_{xy}+dx+ey+f=0$

$u_{xy}=-dx-ey-f$

$u_x=\int(-dx-ey-f)~dy$

$u_x=C(x)-dxy-\dfrac{ey^2}{2}-fy$

$u=\int\left(C(x)-dxy-\dfrac{ey^2}{2}-fy\right)dx$

$u=C_1(x)+C_2(y)-\dfrac{dx^2y}{2}-\dfrac{exy^2}{2}-fxy$

Case $2$: $a\neq0$ and $b=c=0$

Then $u_{xy}+au_x+dx+ey+f=0$

Let $u_x=v$ ,

Then $u_{xy}=v_y$

$\therefore v_y+av+dx+ey+f=0$

$v_y+av=-dx-ey-f$

$(\exp(ay)v)_y=-dx\exp(ay)-ey\exp(ay)-f\exp(ay)$

$\exp(ay)v=\int(-dx\exp(ay)-ey\exp(ay)-f\exp(ay))~dy$

$\exp(ay)u_x=C(x)-\dfrac{dx\exp(ay)}{a}-\dfrac{ey\exp(ay)}{a}+\dfrac{e\exp(ay)}{a^2}-\dfrac{f\exp(ay)}{a}$

$u_x=C(x)\exp(-ay)-\dfrac{dx}{a}-\dfrac{ey}{a}+\dfrac{e}{a^2}-\dfrac{f}{a}$

$u=\int\left(C(x)\exp(-ay)-\dfrac{dx}{a}-\dfrac{ey}{a}+\dfrac{e}{a^2}-\dfrac{f}{a}\right)dx$

$u=C_1(x)\exp(-ay)+C_2(y)-\dfrac{dx^2}{2a}-\dfrac{exy}{a}+\dfrac{ex}{a^2}-\dfrac{fx}{a}$

Case $3$: $b\neq0$ and $a=c=0$

Then $u_{xy}+bu_y+dx+ey+f=0$

Let $u_y=v$ ,

Then $u_{xy}=v_x$

$\therefore v_x+bv+dx+ey+f=0$

$v_x+bv=-dx-ey-f$

$(\exp(bx)v)_x=-dx\exp(bx)-ey\exp(bx)-f\exp(bx)$

$\exp(bx)v=\int(-dx\exp(bx)-ey\exp(bx)-f\exp(bx))~dx$

$\exp(bx)u_y=C(y)-\dfrac{dx\exp(bx)}{b}+\dfrac{d\exp(bx)}{b^2}-\dfrac{ey\exp(bx)}{b}-\dfrac{f\exp(bx)}{b}$

$u_y=C(y)\exp(-bx)-\dfrac{dx}{b}+\dfrac{d}{b^2}-\dfrac{ey}{b}-\dfrac{f}{b}$

$u=\int\left(C(y)\exp(-bx)-\dfrac{dx}{b}+\dfrac{d}{b^2}-\dfrac{ey}{b}-\dfrac{f}{b}\right)dy$

$u=C_1(x)+C_2(y)\exp(-bx)-\dfrac{dxy}{b}+\dfrac{dy}{b^2}-\dfrac{ey^2}{2b}-\dfrac{fy}{b}$

Case $4$: $a,b,c\neq0$

Then $u_{xy}+au_x+bu_y+cu+dx+ey+f=0$

Try let $u=p(x)q(y)v$ ,

Then $u_x=p(x)q(y)v_x+p_x(x)q(y)v$

$u_y=p(x)q(y)v_y+p(x)q_y(y)v$

$u_{xy}=p(x)q(y)v_{xy}+p(x)q_y(y)v_x+p_x(x)q(y)v_y+p_x(x)q_y(y)v$

$\therefore p(x)q(y)v_{xy}+p(x)q_y(y)v_x+p_x(x)q(y)v_y+p_x(x)q_y(y)v+a(p(x)q(y)v_x+p_x(x)q(y)v)+b(p(x)q(y)v_y+p(x)q_y(y)v)+cp(x)q(y)v+dx+ey+f=0$

$p(x)q(y)v_{xy}+p(x)(q_y(y)+aq(y))v_x+(p_x(x)+bp(x))q(y)v_y+(p_x(x)q_y(y)+ap_x(x)q(y)+bp(x)q_y(y)+cp(x)q(y))v=-dx-ey-f$

Take $q_y(y)+aq(y)=0\Rightarrow q(y)=\exp(-ay)$ and $p_x(x)+bp(x)=0\Rightarrow p(x)=\exp(-bx)$ , the PDE becomes

$\exp(-bx-ay)v_{xy}+(c-ab)\exp(-bx-ay)v=-dx-ey-f$

$v_{xy}+(c-ab)v=-dx\exp(bx+ay)-ey\exp(bx+ay)-f\exp(bx+ay)$

Case $4a$: $c=ab$

Then $v_{xy}=-dx\exp(bx+ay)-ey\exp(bx+ay)-f\exp(bx+ay)$

$v_x=\int(-dx\exp(bx+ay)-ey\exp(bx+ay)-f\exp(bx+ay))~dy$

$v_x=C(x)-\dfrac{dx\exp(bx+ay)}{a}-\dfrac{ey\exp(bx+ay)}{a}+\dfrac{e\exp(bx+ay)}{a^2}-\dfrac{f\exp(bx+ay)}{a}$

$v=\int\left(C(x)-\dfrac{dx\exp(bx+ay)}{a}-\dfrac{ey\exp(bx+ay)}{a}+\dfrac{e\exp(bx+ay)}{a^2}-\dfrac{f\exp(bx+ay)}{a}\right)dx$

$\exp(bx+ay)u=C_1(x)+C_2(y)-\dfrac{dx\exp(bx+ay)}{ab}+\dfrac{d\exp(bx+ay)}{ab^2}-\dfrac{ey\exp(bx+ay)}{ab}+\dfrac{e\exp(bx+ay)}{a^2b}-\dfrac{f\exp(bx+ay)}{ab}$

$\exp(bx+ay)u=C_1(x)+C_2(y)-\dfrac{(dx+ey+f)\exp(bx+ay)}{ab}+\dfrac{d\exp(bx+ay)}{ab^2}+\dfrac{e\exp(bx+ay)}{a^2b}$

$u=C_1(x)\exp(-bx-ay)+C_2(y)\exp(-bx-ay)-\dfrac{dx+ey+f}{ab}+\dfrac{d}{ab^2}+\dfrac{e}{a^2b}$

$u=C_1(x)\exp(-ay)+C_2(y)\exp(-bx)-\dfrac{dx+ey+f}{ab}+\dfrac{d}{ab^2}+\dfrac{e}{a^2b}$

Hence the really difficult case is that when $c\neq ab$ . By letting $u=\exp(-bx-ay)v$ the PDE will reduce to $v_{xy}+(c-ab)v=-dx\exp(bx+ay)-ey\exp(bx+ay)-f\exp(bx+ay)$ , which is as headache as about the PDE $u_{xy}+f(x)g(y)u=0$ for finding its most general solution.

share|improve this answer
1  
Most text books just show how to solve the standard second order PDE. I thought it was easy to handle linear terms which turns out to be not. Anyway, thank you very much! –  hxhxhx88 Nov 7 '12 at 14:32

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.